The Systemic Effects of Blood Flow Restriction Training: A Systematic Review - Bradley C Miller; Alexander W Tirko; Justin M Shipe; Olivia R Sumeriski; Kelley Moran (International Journal of Sports Physical Therapy)
# Background Blood flow restriction (BFR) training has been reported to have significant benefits on local skeletal muscle including increasing local muscle mass, strength, and endurance while exercising with lower resistance. As a result, patients unable to perform traditional resistance training may benefit from this technique. However, it is unclear what effects BFR may have on other body systems, such as the cardiovascular and pulmonary systems. It is important to explore the systemic effects of BFR training to ensure it is safe for use in physical therapy.